Optogenetic self-stimulation in the nucleus accumbens: D1 reward versus D2 ambivalence - Cole, Shannon L.; Robinson, Mike J. F.; Berridge, Kent C. (PloS one, 2018)
The nucleus accumbens (NAc) contains multiple subpopulations of medium spiny neurons (MSNs). One subpopulation expresses D1-type dopamine receptors, another expresses D2-type receptors, and a third expresses both. The relative roles in NAc of D1 neurons versus D2 neurons in appetitive motivation were assessed here. Specifically, we asked whether D1-Cre mice would instrumentally seek optogenetic self-stimulation specifically targeted at D1 MSNs in NAc, and similarly if D2-Cre mice would self-stimulate D2 neurons in NAc. Mice were implanted with Cre-targeted channelrhodopsin (ChR2) virus and optic fibers in NAc. Subsequently, mice could earn brief NAc laser illuminations by actively touching a metal spout in one task, or by going to a particular location in a separate task. Results indicated that D1 neuronal excitation in NAc supported intense self-stimulation in both tasks. D1-Cre mice earned hundreds to thousands of spout-touches per half-hour session, and also sought out locations that delivered NAc laser to excite D1 MSNs. By comparison, D2 ChR2 mice showed lower but still positive levels of self-stimulation in the spout-touch task, earning dozens to hundreds of NAc laser illuminations. However, in the location task, D2 mice failed to show positive self-stimulation. If anything, a few D2 individuals gradually avoided the laser location. Brain-wide measures indicated that D1 and D2 stimulations in NAc recruited heavily overlapping patterns of Fos activation in distant limbic structures. These results confirm that excitation of D1 MSNs in NAc supports strong incentive motivation to self-stimulate. They also suggest that excitation of D2 neurons in NAc supports self-stimulation under some conditions, but fails under others and possibly may even shift to negative avoidance.